UPAYA MENINGKATKAN KECEPATAN TENDANGAN MAEGERI CHUDAN MELALUI MODIFIKASI LATIHAN SQUAT JUMPS DAN LATIHAN SPLIT JUMPS PADA ATLET KARATE WADOKAI DOJO SMA NEGERI 11 MEDAN - Pangondian Hotliber Purba; Sabaruddin Yunis Bangun; David Siahaan (Journal Physical Education, Health and Recreation, 2019)
This study aims to increase the speed of the maegery chudan with modification of squat jumps and split jumps in karate. The subjects were Wadokai karateka in dojo SMA Negeri 11 Medan, They are totaling 10 athletes. The instrument is the speed test of maegery chudan and using a stopwatch. Based on the pre-test results it turns out that 10 athletes or overall Wadokai dojo karate athletes in Medan 11 High School have not reached the limit of achieving personal and group targets. Of the 10 athletes, there are no athletes who have achieved personal targets and group achievement limits of 0% with the average athlete's ability score of 76.14%.            The methodology used in this study is Class Action Research. The results of the first cycle after being given treatment in the form of modification of squat jumps and split jumps. Of the 10 athletes, there were 8 athletes (80%) who had reached the personal target limit, 2 athletes (20%) who had not reached the personal target limit and a group achievement limit of 80% with an average athlete's ability score of 82.41%. Based on the results of data analysis it can be said that through the application of modification exercises in squat jumps and split jumps training can increase the speed of the chudan kicks in the Wadokai dojo karate athletes in Medan 11 Public High School in 2018